Migrant subjectivities and temporal flexibility of East‐Central European labour migration to the United Kingdom - Sergei Shubin (Population, Space and Place, 2021)
This paper seeks to broaden existing understandings of migrant worker flexibility drawing on the data from the two ethnographic studies of low-wage employers and Eastern European migrants in Scotland. It focuses on the temporal aspects of flexibility production in employment discourse and temporal expectations about flexible migrant workers. Our findings reveal double movement of interruption and re-making of temporal flexibility, which challenges directional expectations about time and unsettles the assumed connectivity between flexibility’s temporal elements. Uncertainty and instability of migration and employment frameworks undermine the attempts of employers and migrants to manage time, to develop continuous portfolio careers and coherent temporal horizons. Furthermore, contested temporal expectations about flexible migrant workers create fragmented and fractured ‘flexiworkers’ that do not fit within the existing temporal frameworks of signs, routines and rhythms. The paper suggests re-orientation of flexibility debates beyond temporal measurement, outside familiar temporal structures and towards re-definition of flexible worker identities.